Brain Injury with Sickle Cell Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
The relationship between brain injury and vasculopathy in 146 sickle cell (SCD) patients with hemoglobin SS, the most serious form of SCD, was evaluated by MRI and MRA at St Jude Children's Research Hospital, Memphis, TN.